Service quality: a study on taxi drivers at Koperasi Permodalan Melayu Negeri Johor Berhad (KPMNJ) / Masliana Mustaffa - Mustaffa, Masliana (Faculty of Business and Management, 2009)
This research is all about Service Quality : A Study On Taxi Drivers At Koperasi Permodalan Melayu Negeri Johor Berhad (KPMNJ). Since the operation of 100 taxis fully started in February 2009, the outstanding of their monthly payment increasing gradually. Factors such as service quality have been identified in order to investigate whether there is a problem with the service quality of KPMNJ or the taxi driver have their own problems in settled the payment. The objective of this research is to identify the level of service quality provided by KPMNJ, to identify the factors that contributing to the service quality of KPMNJ, to identify the most factors contributing to the service quality of KPMNJ, to identify the correlation between all variable in this study and to provide suggestion/recommendation to KPMNJ to improve their service quality. The method in this research will use probability. This is because the nature of research is conclusive research. The techniques is simple random sampling because easy to implement and cost effective. Sample size of this research is 80 taxi drivers of KPMNJ. Survey method focused on personal interview is used in this research. This is because it is simple to administer, the data obtain are reliable because the response are limited to the alternative stated. The mean value for level of service quality, 3.8125 shows that most of the respondents are agree with the service quality provided by KPMNJ. There is significant and positive relationship between all the independent variables (tangible, assurance, reliability, empathy and responsiveness) and dependent variable (service quality). The most factors contributing to the service quality of KPMNJ are tangible and reliability. There is also correlation between it.